LITHOLOGICAL STRUCTURE, OCCURRENCE AND DIDTRIBUTION OF THE LOWER ALBIAN DEPOSITS IN THE PLAIN CRIMEA - KYSELEVYCH, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main lithofacial types of the Lower Albian deposits have been described.